Distinct Visual Thresholds for Egocentric and Allocentric Information Pick UP? - Matthieu De Wit; John Van Der Kamp; Rich Masters (i-Perception, 2011)
Unlike perceptual size judgments, actions—but not delayed actions—performed under full vision are relatively unaffected by the Müller-Lyer illusion. Controversy remains as to the source of these effects. We aimed to illuminate the problem by exploiting the possibility that vision for action and perception may have distinct thresholds. In Experiment 1 participants performed delayed pointing movements towards briefly presented (12 ms–masked) M-L targets of different sizes. While participants were unable to perceptually discriminate between targets, their movements were nevertheless a function of target size, but not of the illusion (de Wit, van der Kamp, & Masters, in press). This implies 1) that vision for action is functional even after a delay and/or 2) that distinct thresholds exists for egocentric and allocentric information pick up, possibly irrespective of whether a task is perceptual or motoric in nature. Experiment 2, in which participants manually matched the size of perceptually indiscriminable M-L targets, supports the latter option. These findings are reviewed in relation to recent discussions of the two-visual-systems model. de Wit, M.M., van der Kamp, J., & Masters, R.S.W. (in press). Delayed pointing movements to masked Müller-Lyer figures are affected by target size but not the illusion. Neuropsychologia .